소아청소년기에 발생한 골관절염의 임상 양상 및 원인균에 대한 고찰 - 이소영; So Young Lee; 김한울; Han Wool Kim; 조혜경; Hye-kyung Cho; 윤여헌; Yoe Hon Yun; 유경하; Kyung Ha Ryu; 김경효; Kyung-hyo Kim (Pediatric infection & vaccine, 2015)
목적: 소아청소년기의 골관절염은 드물지만 진단과 치료가 지연되는 경우 영구적인 장애를 초래할 수있는 중요한 질환이다. 본 연구에서는 소아청소년기에 발생하는 골관절염의 임상 양상과 원인균을 분석하여 이 질환의 조기 진단과 적절한 항균제 선택에 도움이 되고자 하였다. 방법: 18세 이하의 환자로 2008년 3월부터 2015년 3월까지 이화여대 목동병원 소아청소년과와 정형외과에서 골관절염으로 치료를 받은 42례의 의무기록을 후향적으로 분석하였다. 결과: 42례 중 골수염, 화농성 관절염, 화농성 관절염을 동반한 골수염이 각각 21례, 13례, 8례였다. 남아와 여아는 각각 31명과 11명이었으며, 평균 연령은 7.1세였다. 가장 흔한 임상 증상은 통증과 발병 부위의 압통이었다. 골수염은 대퇴뼈(10례, 34.5%)와 정강이뼈(7례, 24.1%), 화농성 관절염은 고관절(9례, 42.9%)과 무릎 관절(5례, 23.8%)에 주로 발생하였다. 혈청 CRP와 ESR의 상승이 각각 37례(88.1%)에서 관찰되었다. 40례에서 MRI가 시행되었고, 병변의 발견 및 진단에 유용하였다. 혈액 배양 검사가 시행된 38례 중 9례(23.7%), 감염 조직 배양 검사가 시행된 40례 중 20례(50.0%)에서 원인균이 동정되었다. 가장 흔한 원인균은 S. aureus 였으며, 혈액 배양에서 8례(88.9%), 감염 조직 배양에서 14례(70.0%)가 동정되었다. S. aureus 가 동정된 22례중 9례(41.0%)에서 메티실린 내성을 보였다. 결론: 소아청소년기의 골관절염의 가장 흔한 원인균은 S. aureus 로 MRSA의 비중이 41%에 이른다. 따라서 초기 치료제로 반코마이신을 사용할 것을 제안하며, 추후 MRSA 비율에 따른 항균제 선택의 치료 지침에 대한 연구가 필요할 것으로 사료된다. Purpose: Osteoarticular infections in children and adolescents are important because it can cause functional compromise if appropriate treatment is delayed. Therefore, this study was designed to describe the clinical presentations and causative organisms of osteoarticular infections in children and adolescents in order to propose early diagnosis method and an appropriate empiric antimicrobial therapy. Methods: Forty-two medical records were reviewed retrospectively, which were confirmed as osteomyelitis (OM) or septic arthritis (SA) at Department of Pediatrics or Orthopedic Surgery in patients under 18 years old of Ewha Womans University Mokdong Hospital from March 2008 to March 2015. Results: We identified 21 cases of OM, 13 cases of SA and 8 cases of OM with SA. There were 31 males and 11 females and mean age was 7.1 years old. The most common symptoms were pain and tenderness of involved site. Major involved bones were femur (10 cases, 34.5%), tibia (7 cases, 24.1%) and major involved joints were hip (9 cases, 42.9%), and knee (5 cases, 23.8%). Increased serum C-reactive protein and erythrocyte sedimentation rate were observed in 37 cases (88.1%) respectively. Magnetic resonance imaging was performed in 40 cases among 42 cases and was used to demonstrate osteoarticular infections and other adjacent infections. Nine cases (23.7%) among 38 cases and 20 cases (50.0%) among 40 cases were positive in blood culture and infected site culture respectively. The most common causative organism was Staphylococcus aureus , which was represented in 22 cases (75.9%), of which nine cases (40.9%) were resistant to methicillin. Conclusions: S. aureus was the most common causative organism of osteoarticular infections in children and adolescents and the proportion of MRSA was high in this study. Therefore, we recommend vancomycin as the first empiric antimicrobial therapy and suggest that further study is necessary to elucidate an appropriate guideline for treatment which takes into account MRSA proportion.